Determination of Intention to Use Digital Payment Mediated by Cashback Promotion - Suciningsih, Made Rita; Maradona, Agus Fredy (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research explores the factors that influence the intention to use digital payment systems, focusing specifically on the Millennial and Generation Z populations in Bali. By employing the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT), the study aims to enhance the existing academic literature on technology acceptance and provide valuable insights into user behavior regarding digital payments. Key constructs such as Perceived Usefulness and Perceived Ease of Use are analyzed to determine their effects on user adoption. The results indicate that users who perceive digital payment systems as beneficial and easy to use are more inclined to adopt these technologies, which in turn improves their performance and productivity. This research not only contributes to theoretical frameworks but also offers practical implications for businesses aiming to enhance user satisfaction and maintain a competitive edge in the digital payment sector